Flexible Sb0.405Te0.595 photodetectors with broadband spectral response up to 4.5 µm. (March 2022) - Zhou, Hongxi; Liu, Shukai; Yang, Ming; Liu, Xianchao; Zhang, Xingchao; Zhou, Xin; Han, Jiayue; Gou, Jun; Wang, Jun; Jiang, Yadong
Abstract: As one of the third-generation topological insulators (TIs), antimony telluride (Sb2 Te3 ) is considered as a prospective candidate for extremely sensitive and broadband photodetectors ascribed to its extremely narrow direct band gap and exotic optical properties. However, due to the ultrafast carrier recombination time and small carrier lifetime of Sb2 Te3, it continues to be an enormous challenge to achieve broadband detection in the mid-wave infrared (MWIR) region. Here, distinctive broadband photodetectors based on stable and scalable high-quality Sn-catalyzed Sb0.405 Te0.595 films grown by physical vapor deposition (PVD) was described, and they were found to be photoconductive and sensitive in the visible light (VL) - MWIR region (405–4500 nm). The optimized responsivity (Ri ) and specific detectivity (D*) of photodetectors achieved 588 A/W and 6.435 × 10 8 Jones, respectively. Additionally, these devices exhibit fantastic mechanical flexibility, durability and stability following 200 bending cycles without obvious degradation of photoelectric performance. These excellent properties provide new strategy and insight into the manufacture of high-performance and wearable photodetectors for energy efficient nanoelectronics. Graphical abstract: Our method presents a potential application of topological insulators based photodetectors with a promising candidate for wearable optoelectronics. Image, graphical abstract